Analysis of Persuasive Communication between Teachers and Parents in Foresting Independence in Six Years Old Children - Eka Dewi Wulandari; Melia Dwi Widayanti; Sri Setyowati; Mallevi Agustin Ningrum (Kumara Cendekia, 2026)
Independence in early childhood is an important aspect of character development. Among 13 children, Ananda EAS demonstrated the most prominent level of independence. Communication plays a crucial role in fostering children's independence. This study aims to analyze the implementation of persuasive communication by teachers and parents in developing children's independence. This research employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model. The results show that teachers and parents apply persuasive communication in different but complementary ways. Teachers use a fun and structured approach in learning activities, while parents apply a gentle and emotional approach in daily life. The consistent use of persuasive communication contributes to the development of children's independence, particularly in responsibility and discipline. However, the aspect of sharing at school and responsibility at home still needs improvement.